Improving Economic Community Empowerment and Health Care Utilization through Insurance Awareness to Reduce Maternal Death in Indonesia - Murti, Nugroho Wisnu; Widyaningsih, Vitri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Maternal mortality is still a global public health problem. Despite the efforts that have been conducted to prevent maternal death, the rate remains high, especially in the low and middleincome country. Indonesia faced a big challenge, with increased number of maternal mortality in recent years which has reached more than 300 deaths per 100,000 live births, and fails to reach its Millennium Development Goal (MDGs) in 2015 of 102 maternal deaths per 100,000 live births. Several factors that have been related to maternal death include hemorrhage, hypertension, and infection as three main direct causes of maternal mortality. Several indirect causes include maternal preexisting medical problems, such as diabetes, anemia, HIV and chronic energy malnutrition. Problems regarding access and quality of health care, especially during the antenatal and postpartum period have also been linked to maternal mortality. With the current policy of universal coverage, maternal health care should reach women from all socioeconomic background which will alleviate this problem. It is also crucial to improve income to ensure that these women can afford insurance membership, especially those who are not covered by the government. This paper reviewed methods to decrease maternal mortality through increasing health care utilization by improving insurance awareness and community empowerment in economics which will enable women to have adequate access to quality health care.